Answer:
A function is a relation in which each possible input value leads to exactly one output value
Question:
Which is equivalent to
after it has been simplified completely?
Answer:
![\sqrt{180x^{11}} = 6x^{5}\sqrt{5x}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206x%5E%7B5%7D%5Csqrt%7B5x%7D)
Step-by-step explanation:
Given
![\sqrt{180x^{11}}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D)
Required
Simplify
We start by splitting the square root
![\sqrt{180x^{11}} = \sqrt{180} * \sqrt{x^{11}}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%20%5Csqrt%7B180%7D%20%2A%20%5Csqrt%7Bx%5E%7B11%7D%7D)
Replace 180 with 36 * 5
![\sqrt{180x^{11}} = \sqrt{36 * 5} * \sqrt{x^{11}}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%20%5Csqrt%7B36%20%2A%205%7D%20%2A%20%20%5Csqrt%7Bx%5E%7B11%7D%7D)
Further split the square roots
![\sqrt{180x^{11}} = \sqrt{36} *\sqrt{5} * \sqrt{x^{11}}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%20%5Csqrt%7B36%7D%20%2A%5Csqrt%7B5%7D%20%2A%20%20%5Csqrt%7Bx%5E%7B11%7D%7D)
![\sqrt{180x^{11}} = 6*\sqrt{5} * \sqrt{x^{11}}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206%2A%5Csqrt%7B5%7D%20%2A%20%20%5Csqrt%7Bx%5E%7B11%7D%7D)
Replace power of x; 11 with 10 + 1
![\sqrt{180x^{11}} = 6*\sqrt{5} * \sqrt{x^{10 + 1}}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206%2A%5Csqrt%7B5%7D%20%2A%20%20%5Csqrt%7Bx%5E%7B10%20%2B%201%7D%7D)
From laws of indices; ![a^{m+n} = a^m * a^n](https://tex.z-dn.net/?f=a%5E%7Bm%2Bn%7D%20%3D%20a%5Em%20%2A%20a%5En)
So, we have
![\sqrt{180x^{11}} = 6*\sqrt{5} * \sqrt{x^{10} * x^1}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206%2A%5Csqrt%7B5%7D%20%2A%20%20%5Csqrt%7Bx%5E%7B10%7D%20%2A%20x%5E1%7D)
![\sqrt{180x^{11}} = 6*\sqrt{5} * \sqrt{x^{10} * x}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206%2A%5Csqrt%7B5%7D%20%2A%20%20%5Csqrt%7Bx%5E%7B10%7D%20%2A%20x%7D)
Further split the square roots
![\sqrt{180x^{11}} = 6*\sqrt{5} * \sqrt{x^{10}} * \sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206%2A%5Csqrt%7B5%7D%20%2A%20%20%5Csqrt%7Bx%5E%7B10%7D%7D%20%2A%20%5Csqrt%7Bx%7D)
From laws of indices; ![\sqrt{a} = a^{\frac{1}{2}}](https://tex.z-dn.net/?f=%5Csqrt%7Ba%7D%20%3D%20a%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D)
So, we have
![\sqrt{180x^{11}} = 6*\sqrt{5} * x^{10*\frac{1}{2}} * \sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206%2A%5Csqrt%7B5%7D%20%2A%20%20x%5E%7B10%2A%5Cfrac%7B1%7D%7B2%7D%7D%20%2A%20%5Csqrt%7Bx%7D)
![\sqrt{180x^{11}} = 6*\sqrt{5} * x^{\frac{10}{2}} * \sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206%2A%5Csqrt%7B5%7D%20%2A%20%20x%5E%7B%5Cfrac%7B10%7D%7B2%7D%7D%20%2A%20%5Csqrt%7Bx%7D)
![\sqrt{180x^{11}} = 6*\sqrt{5} * x^{5} * \sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206%2A%5Csqrt%7B5%7D%20%2A%20%20x%5E%7B5%7D%20%2A%20%5Csqrt%7Bx%7D)
Rearrange Expression
![\sqrt{180x^{11}} = 6 * x^{5} * \sqrt{5} * \sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206%20%2A%20%20x%5E%7B5%7D%20%2A%20%5Csqrt%7B5%7D%20%2A%20%5Csqrt%7Bx%7D)
![\sqrt{180x^{11}} = 6x^{5} * \sqrt{5} * \sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206x%5E%7B5%7D%20%2A%20%5Csqrt%7B5%7D%20%2A%20%5Csqrt%7Bx%7D)
From laws of indices; ![\sqrt{a} *\sqrt{b} = \sqrt{a*b} = \sqrt{ab}](https://tex.z-dn.net/?f=%5Csqrt%7Ba%7D%20%2A%5Csqrt%7Bb%7D%20%3D%20%5Csqrt%7Ba%2Ab%7D%20%3D%20%5Csqrt%7Bab%7D)
So, we have
![\sqrt{180x^{11}} = 6x^{5} * \sqrt{5*x}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206x%5E%7B5%7D%20%2A%20%5Csqrt%7B5%2Ax%7D)
![\sqrt{180x^{11}} = 6x^{5} * \sqrt{5x}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206x%5E%7B5%7D%20%2A%20%5Csqrt%7B5x%7D)
![\sqrt{180x^{11}} = 6x^{5}\sqrt{5x}](https://tex.z-dn.net/?f=%5Csqrt%7B180x%5E%7B11%7D%7D%20%3D%206x%5E%7B5%7D%5Csqrt%7B5x%7D)
<em>The expression can no longer be simplified</em>
Hence,
is equivalent to ![6x^{5}\sqrt{5x}](https://tex.z-dn.net/?f=6x%5E%7B5%7D%5Csqrt%7B5x%7D)
Answer:
u just add it
Step-by-step explanation:
Answer:
4%
Step-by-step explanation:
1000 of 25000 is 4%
The first term of the arithmetic progression exists at 10 and the common difference is 2.
<h3>
How to estimate the common difference of an arithmetic progression?</h3>
let the nth term be named x, and the value of the term y, then there exists a function y = ax + b this formula exists also utilized for straight lines.
We just require a and b. we already got two data points. we can just plug the known x/y pairs into the formula
The 9th and the 12th term of an arithmetic progression exist at 50 and 65 respectively.
9th term = 50
a + 8d = 50 ...............(1)
12th term = 65
a + 11d = 65 ...............(2)
subtract them, (2) - (1), we get
3d = 15
d = 5
If a + 8d = 50 then substitute the value of d = 5, we get
a + 8
5 = 50
a + 40 = 50
a = 50 - 40
a = 10.
Therefore, the first term is 10 and the common difference is 2.
To learn more about common differences refer to:
brainly.com/question/1486233
#SPJ4